Pengaruh Kajian Praktik Lapangan (KPL) dan Pembelajaran Microteaching Terhadap Kesiapan Mengajar Mahasiswa Prodi Pendidikan Teknik Mesin Universitas Negeri Malang - ahmad habib galangrendika (Jurnal Teknik Mesin dan Pembelajaran, 2020)
KPL and mictroteaching study are course programs of education as an effort to equip and give an experience of real teaching to education students. This study used ex post facto research method with quantitative approach. Population and sample of this study were Mechanical Engineering Education students of 2015 generation. Instrument used in this study as data collecting technique was an questionnaire. Results of study: 1) Analysis result of hypothesis test of KPL showed significance (0,001 < 0,05). 2) Analysis result of hypothesis test of microteaching study showed significance (0,000 > 0,05). 3) Analysis result of F test (simultaneity test) KPL and microteaching study showed significance (0,000 < 0,05) and Fcount  > Ftable (57,642 > 3,11).Keywords: Kajian Praktik Lapangan (KPL), Microteaching Study, Readiness in Teaching